(untitled) (International Journal of Engineering Management Science, 2023)
The use of renewable energy sources is being promoted by governmental and non-governmental organization as a greener alternative because the world’s resources are limited. The fuel required to run the electric cars that are the focus of current research is electricity. Car chargers for electric automobiles are an efficient and workable solution to the energy dilemma. Since petroleum supplies are running low, we need to find alternative sources of energy to meet our everyday needs. From this perspective, we wanted to offer a feasible, reasonable, and functional concept for an RFID-enabled photovoltaic charging station for electric vehicles. This is how charging an electric vehicle (EV) actually occurs; the object being charged is displayed through an RFID card.